Sharing of Worldwide Spread Knowledge Using Hypermedia Facilities & Fast Communication Protocols (Mosaic and World Wide Web): The Example of ExPASy - Hochstrasser, D. F.; Appel, R. D.; Golaz, O.; Pasquali, Ch.; Sanchez, J.-C.; Bairoch, A. (Methods of Information in Medicine, 1995)
The sharing of knowledge worldwide using hypermedia facilities and fast communication protocols (i.e., Mosaic and World Wide Web) provides a growth capacity with tremendous versatility and efficacy. The example of ExPASy, a molecular biology server developed at the University Hospital of Geneva, is striking. ExPASy provides hypermedia facilities to browse through several up-to-date biological and medical databases around the world and to link information from protein maps to genome information and diseases. Its extensive access is open through World Wide Web. Its concept could be extended to patient data including texts, laboratory data, relevant literature findings, sounds, images and movies. A new hypermedia culture is spreading very rapidly where the international fast transmission of documents is the central element. It is part of the emerging new “information society”.
Keywords: Mosaic; World Wide Web